Two Way Indicator Species Analysis (TWINSPAN) of the Herbaceous Vegetation in an Inland Wetland Ecosystem of Doon Valley Himalaya, India - Manhas, R. K.; Gautam, M. K.; Kumari, Deepa (Journal of Wetlands Ecology, 2009)
In swamp distribution, dominance and survival of a species is very much governed by the soil moisture and period of flooding. The present study was conducted to classify the communities and plant species, and to have an idea about various associations of plants present in the swamp with respect to soil moisture. Two way indicator species analysis (TWINSPAN) classified the communities into four and plant species into eleven groups. The communities with least soil moisture were the first to be segregated and with highest soil moisture last. Similarly, the species growing in drier condition was clustered separately from the moisture loving indigenous species. Key words: TWINSPAN; vegetation; inland wetland; India DOI: 10.3126/jowe.v3i0.2433 Journal of Wetlands Ecology, (2009) Vol. 3, pp 23-31